The credibility of the official government spokesman to the Iraqi public / Survey Study - Abdel Amir, Ali Abdel Hadi (ALBAHITH ALALAMI, 2018)
The official spokesperson considered responsible for the transmission of information and communication messages that convey the government’s view on the various political and economic issues that affect the public opinion towards the performance achieved by the various governmental institutions and for the purpose of communicating with the media in a positive and effective manner, a number of institutions in the world in general and in Iraq in particular have nominated a spokesman to coordinate the efforts and the dissemination of news and the preparation of press conferences to contribute to the achievement of a positive and effective level between the government and the media, so this study has tackled to deal with the credibility of the government official spokesman to the public as an important factor reflected on the nature of the public reception and the image of his media and professional performance, especially during crisis, through questionnaire distributed in Baghdad and Sulaymaniyah on (181) individuals and the study has reached a number of results: 1. The task of the media spokesperson to invite the media to clarify the government position regarding its relations with the neighboring countries has come the first rank and with an average of (3.6). 2. The official spokesperson of the Iraqi government has a high level of credibility among the public. The high level of credibility of the official spokesman was achieved at 100 frequency and a percentage of 5